2018
DOI: 10.2147/dddt.s156123
|View full text |Cite
|
Sign up to set email alerts
|

Berberine nanoparticles with enhanced in vitro bioavailability: characterization and antimicrobial activity

Abstract: BackgroundBerberine is an isoquinoline alkaloid widely used in Ayurveda and traditional Chinese medicine to treat illnesses such as hypertension and inflammatory conditions, and as an anticancer and hepato-protective agent. Berberine has low oral bioavailability due to poor aqueous solubility and insufficient dissolution rate, which can reduce the efficacy of drugs taken orally. In this study, evaporative precipitation of nanosuspension (EPN) and anti-solvent precipitation with a syringe pump (APSP) were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(88 citation statements)
references
References 43 publications
(47 reference statements)
2
65
0
6
Order By: Relevance
“…The physical state and drug interaction of the system was evaluated via differential scanning calorimetry (DSC) and thermal gravimetric (TG) analysis based on the previously method [ 36 ]. The samples were examined using a Q600 instrument (TA Instruments, New Castle, USA) at a heating rate of 10 °C/min from room temperature up to 200 °C under a nitrogen atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…The physical state and drug interaction of the system was evaluated via differential scanning calorimetry (DSC) and thermal gravimetric (TG) analysis based on the previously method [ 36 ]. The samples were examined using a Q600 instrument (TA Instruments, New Castle, USA) at a heating rate of 10 °C/min from room temperature up to 200 °C under a nitrogen atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…Several alkaloids have been reported to present antimicrobial activity, such as berberine ( Figure ), isolated from several species of the Berberidaceae, Runculaceae and Papaveraceae families. Berberine has been used in the treatment of intestinal infections, such as acute gastroenteritis, cholera and bacillary dysentery . The study by Zhang et al.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been reported that BBR can have regular nanostructures, known as BBR nanoparticles (BBRNPs), by triggering its self-assembly in neutral buffer. 19 Sahibzada's group rst reported that BBRNPs can be generated via both syringe pumping anti-solvent precipitation (APSP) and evaporative precipitation of nanosuspension (EPN). 20 Here we introduced an easier way to prepare BBRNPs.…”
Section: Cell Culturementioning
confidence: 99%
“…19 Sahibzada's group rst reported that BBRNPs can be generated via both syringe pumping anti-solvent precipitation (APSP) and evaporative precipitation of nanosuspension (EPN). 20 Here we introduced an easier way to prepare BBRNPs. In order to prepare different concentrations of BBRNP stock solution, for instance 2 mL 100 mg mL À1 BBRNP stock, 200 mg of BBR was weighed and mixed with 2 mL of neutral PBS buffer; the resulting turbid liquid was sonicated in a 55 C water bath for 2-5 min until a transparent yellowish solution was generated.…”
Section: Cell Culturementioning
confidence: 99%